2013
DOI: 10.4236/ojfd.2013.34032
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Wake Shape behind a Wing in Ground Effect Using an Unsteady Discrete Vortex Panel Method

Abstract: The unsteady evolution of trailing vortex sheets behind a wing in ground effect is simulated using an unsteady discrete vortex panel method. The ground effect is included by image method. The present method is validated by comparing the simulated wake roll-up shapes to published numerical results. When a wing is flying in a very close proximity to the ground, the optimal wing loading is parabolic rather than elliptic. Thus, a theoretical model of wing load distributions is suggested, and unsteady vortex evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The torque values were calculated from the difference between balancing weight and the values shown in digital balance (S) by Eq. (3) [19].…”
Section: Wind Turbine Designmentioning
confidence: 99%
“…The torque values were calculated from the difference between balancing weight and the values shown in digital balance (S) by Eq. (3) [19].…”
Section: Wind Turbine Designmentioning
confidence: 99%
“…Furthermore, in their following report (Sutrisno et al, 2017), it is realized that stall delays, identified in 3-D wind turbine forward and backward blade models, are due to the effects of the rolled-up vortex generated by delta formed-hubs. The conclusion has been drawn based on several experimental evidences (Gursul, Wang, & Vardaki, 2007) (Nelson & Pelletier, 2003) (Han & Kinnas, 2013). Sutrisno et al (Sutrisno, Rochmat, et al, n.d.) have realized how the strength of vortex core produced by rolled-up vortices should be intensively investigated especially its effect on the farther regions affected.…”
Section: From Stall-delay To Rolled-up Vortex and Vortex Corementioning
confidence: 99%
“…Cai et al, learned the optimization of wing-trunk arrangement to suspend the start of asymmetrical vortex [46,47]. Using CFD, Bangga et al, explained the computational arrangement effect on a correct guess of an HAWT rotor.…”
Section: Introductionmentioning
confidence: 99%